Association Between VDR and CYP24A1 Polymorphisms, Atopic Dermatitis, and Biochemical Lipid and Vitamin D Profiles in Spanish Population: Case-Control Study - Ricardo González-Tarancón; Nuria Goñi-Ros; Elvira Salvador-Rupérez; Ángela Hernández-Martín; Silvia Izquierdo-Álvarez; José Puzo-Foncillas; Yolanda Gilaberte-Calzada (JMIR Publications, 2023)
BackgroundAtopic dermatitis (AD) is the most prevalent inflammatory skin disorder, characterized by impaired epidermal barrier function and an altered immune response, both of which are influenced by vitamin D deficiency. Single-nucleotide polymorphisms (SNPs) in VDR and CYP24A1 have been previously associated with AD. ObjectiveWe sought to characterize the associations between the VDR and CYP24A1 polymorphisms and the vitamin D and lipid biochemical profile in children diagnosed with AD. MethodsA total of 246 participants (143 patients with AD and 103 healthy controls) were enrolled in this study. Genotyping for polymorphisms in VDR (rs2239185, rs1544410, rs7975232, rs2238136, rs3782905, rs2239179, rs1540339, rs2107301, rs2239182, and rs731236) and CYP24A1 (rs2248359 and rs2296241) was performed by allele-specific polymerase chain reaction using integrated fluidic circuit technology. Serum levels of calcium, phosphorus, and vitamin D were measured, and the biochemical lipid profile was determined. ResultsAmong VDR SNPs, rs2239182 exerted a protective effect against the development of AD, whereas rs2238136 was identified as a risk factor for AD. The GCC haplotype (rs2239185-G, rs1540339-C, and rs2238136-C) appeared to protect against the development of AD. rs2239182-CC was associated with higher 25(OH)D concentrations, whereas rs2238136-TT, rs2239185-GA, and rs2248359-TT were present in a large proportion of patients with serum vitamin D deficiency. rs2239185-AA, rs2239182-CC, and rs1540339-CC were associated with higher serum total cholesterol; rs2239182-TT was associated with lower low-density lipoprotein cholesterol; and rs2239182-TC with lower high-density lipoprotein cholesterol. Both CYP24A1 SNPs (rs2296241-AA and rs2248359-TT) were associated with higher high-density lipoprotein cholesterol levels. ConclusionsThe VDR SNP rs2238136 is a risk factor for AD and other SNPs in VDR and CYP24A1, which may lead to alterations in biochemical parameters that influence the risk of AD. Our findings highlight the complex genetic basis to AD and indicate that interrelationships between different genetic factors can lead to alterations in vitamin D metabolism or lipid profiles, which in turn may influence the development of AD.